2012
DOI: 10.1194/jlr.p023614
|View full text |Cite
|
Sign up to set email alerts
|

Liver fat reduction with niacin is influenced by DGAT-2 polymorphisms in hypertriglyceridemic patients

Abstract: This article is available online at http://www.jlr.org Nonalcoholic fatty liver disease (NAFLD) characterized by excessive accumulation of intrahepatic triglycerides is associated with multiple metabolic abnormalities that are important cardiovascular risk factors, including increased plasma triglycerides (TG), obesity, insulin resistance, diabetes, and the metabolic syndrome ( 1, 2 ). Hepatic steatosis, the earliest stage of the disease, arises from an imbalance between hepatic TG acquisition and removal ( 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 33 publications
6
63
0
Order By: Relevance
“…In order to extend the use of niacin for other indications, we recently showed that niacin prevented the accumulation of fat in liver and regressed pre-existing hepatic steatosis in high-fat fed rat model of NAFLD [16]. In support of our study in experimental NAFLD model, Hu et al in a small uncontrolled study in 39 patients recently showed that niacin therapy (2 g/day) significantly reduced liver fat content in Chinese patients with hypertriglyceridemia [17]. However, hepatocellular mechanisms of action of niacin on pathophysiological events involved in NAFLD are not known.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In order to extend the use of niacin for other indications, we recently showed that niacin prevented the accumulation of fat in liver and regressed pre-existing hepatic steatosis in high-fat fed rat model of NAFLD [16]. In support of our study in experimental NAFLD model, Hu et al in a small uncontrolled study in 39 patients recently showed that niacin therapy (2 g/day) significantly reduced liver fat content in Chinese patients with hypertriglyceridemia [17]. However, hepatocellular mechanisms of action of niacin on pathophysiological events involved in NAFLD are not known.…”
supporting
confidence: 86%
“…Although increased levels of alanine aminotransferase and/or aspartate aminotransferase were observed in some patients taking higher concentrations of niacin as compared to placebo, the levels of these enzymes were not greater than 3 times the upper limit in majority of the patients [57,60]. In fact, in a recent uncontrolled study in dyslipidemic patients with steatosis, niacin administration (2 g/day for 16 weeks) improved liver enzymes including alanine aminotransferase, gammaglutamyl transferase, and alkaline phosphatase [17]. These initial clinical observations are consistent with the potentially beneficial effect of niacin on fat accumulation and antioxidant effects as suggested in this and our original report in a rat NAFLD model [16].…”
Section: Discussionmentioning
confidence: 84%
“…It is now evident that by inhibiting DGAT2, niacin would prevent hepatic steatosis associated with endogenous synthesis of fatty acids. Interestingly, the efficacy of niacin as an agent against fatty liver is dependent on DGAT2 polymorphisms of the individuals studied [94], confirming the central role of the enzyme in determining the rate of de novo TAG synthesis and, in turn, of the absolute rates of net de novo TAG synthesis by the liver.…”
Section: Implications Of the Sequential Action Of Dgat2 And Dgat1mentioning
confidence: 93%
“…In Chinese patients with hypertriglyceridemia extended-release niacin induced a reduction of liver fat content (Hu et al 2012). A polymorphism of DGAT-2 influenced the strength of this effect which demonstrates the significance of DGAT-2 modification within the action of niacin.…”
Section: Mechanisms Of Action Of Niacinmentioning
confidence: 98%